Efficient selective encryption schemes to secure video data and moving objects information for HEVC/H.265 using advanced encryption standard / Mohammed Ahmed Mohammed Saleh - Mohammed Saleh, Mohammed Ahmed (Institute of Graduate Studies, UiTM, 2016)
Due to the huge growth in communication and digital technologies in support of multimedia sharing, video security has recently attracted the attention of researchers. Since video data representation takes up a large amount of data, it has to be minimized before being transmitted through the channels. To do so, that data has to be subjected to a compression process. This process is performed according to the video coding standard (video compression). There have been different types of video coding standards, but High Efficiency Video Coding (HEVC) is the latest video coding standard being introduced. Whereas, in the field of video security, there are several types of encryption algorithms utilized by researchers, such as Rivest- Shamir-Adleman (RSA), Data Encryption Standard (DES) and Advanced Encryption Standard (AES). All of those encryption algorithms are classified as asymmetric and symmetric algorithms. Since the video data is still huge even after the compression process, most researchers apply their encryption approaches on a selective part of the video data whereas the compression process is performed by a different type of coding standard. Most of the existing video encryption methods are not adequate to secure the video contents against the modern security attacks and eavesdropping. Furthermore, those methods have become impractical especially for the video sharing through the internet using the new coding standard HEVC because of the limited resources on the devices…